PENGAMATAN KEBERADAAN BADAK SUMATERA (Dicerorhinus sumatrensis) DI KUTAI BARAT DAN MAHAKAM ULU KALIMANTAN TIMUR - Gusti Hardiansyah; Ahmad Muslim; Gusti Eva Tavita; Yuyun Kurniawan; Arif Data Kusuma (Universitas Tanjungpura, 2013)
Sumatran Rhino (Dicerorhinus sumatrensis) is the smallest rhinoceros and the most primitive types of the five species of rhinoceros that still alive. In the 1990s the status of the Sumatran rhino population in East Kalimantan never again recorded scientifically (Meijaard, 1996). In 2013 WWF Indonesia - Kutai Barat find signs of rhino are supported by the findings of the trail and a video camera recording automatically. The study aims to determine the status of the rhino habitat conditions and population. The experiment was conducted in Kutai Barat and Mahakam Ulu , East Kalimantan. In this study used a grid of 4x4 km ² ² divided into 2x2 cells with an area of 240 km² observations which represent 15 % of Zone 1 ( 1,600 km² ). The results showed high levels of habitat suitability with a population of 7-15 individuals.Key words : Habitat, population Sumatran Rhinoceros (Dicerorhinus sumatrensis)